Effects of age, period, and cohort on the prevalence of frailty in Chinese older adults from 2002 to 2014 - Li, Siying; Fan, Wenye; Zhu, Boya; Ma, Chao; Tan, Xiaodong; Gu, Yaohua (Frontiers in Public Health, 2022)
Background: Currently, longitudinal studies of frailty are in an early stage, particularly in low- and middle-income countries. Only one study was conducted in Hong Kong to examine the age-period-cohort effects on the prevalence of frailty among Chinese older adults. Objectives: This study aims to shed light on the prevalence trajectory of frailty among older adults in mainland China through the APC model and to analyze the effects of age, period and cohort on the prevalence trajectory. Methods: The sample for this study was older adults aged 65-109 years old from the 2002 to 2014 Chinese Longitudinal Healthy Longevity Survey (CLHLS). Frailty status measured by Rockwood FI. Age-period-cohort model was used to describe the effects of age, period and cohort on the prevalence trajectory of frailty. Results: The frailty prevalence among Chinese older adults changed significantly with age, period and cohort. Furthermore, the age effect was much stronger than the period and cohort effects. The prevalence of frailty in the 101-103 and 104-106 age groups were 8.998 (95% CI 13.667-5.924) and 8.699 (95% CI 13.037-5.805) times higher than the 65-67 age group, respectively. Sensitivity analysis based on Fried frailty phenotype showed similar results, confirming the robustness of our findings. Conclusion: All of the age effect reflecting the individual ageing process, period effect reflecting the change in the social environment and birth cohort effect reflecting different generations could influence the prevalence of frailty at the population level. In contrast, the age effect was the main effect.